Manajemen Usaha Dan Pembuatan Kemasan Serta Labeling Home Industri Bakso Aci Pada Usaha Kelompok Warga Kahuripan Nirwana Sidoarjo - Hapsari, Yola Rizki (Jurnal Dehasen Mengabdi, 2024)
With the home industry business of aci meatballs, the Kahuripan Nirwana Sidoarjo Residents Group, which already has regular customers, will increase its marketing by making attractive packaging and labels to find a market and even agents who want to sell it, so that there will be many who will help to develop this aci meatball business. The problems faced are (1) entrepreneurial management has not been implemented optimally (2) good packaging has not been provided for the aci meatball products being marketed and (3) labeling has not been provided to introduce the product. The stages of implementing the service that have been carried out to date are: assisting with packaging by providing assistance in the form of tools to glue packaging ready for market so that it looks neat, helping to make attractive labels on packaging by replacing old labels; help carry out promotions by placing small banners in front of Partner's house. The expected result at this stage is an increase in the number of buyers / customers from our partners, namely the Home Industry of Meatballs and the Kahuripan Nirwana Sidoarjo Group. The next stage is evaluation of the results of entrepreneurial management assistance, packaging and labeling creation.